YAP1 alleviates sepsis-induced acute lung injury via inhibiting ferritinophagy-mediated ferroptosis - Zhang, Jing; Zheng, Yongping; Wang, Yun; Wang, Jin; Sang, Aming; Song, Xuemin; Li, Xinyi (Frontiers in Immunology, 2022)
Ferroptosis is a phospholipid peroxidation-mediated and iron-dependent cell death form, involved in sepsis-induced organ injury and other lung diseases. Yes-associated protein1 (YAP1), a key regulator of the Hippo signaling pathway, could target multiple ferroptosis regulators. Herein, this study aimed to explore the involvement of ferroptosis in the etiopathogenesis of sepsis-induced acute lung injury (ALI) and demonstrate that YAP1 could disrupt ferrintinophagy and moderate sepsis-induced ALI. Cecal ligation and puncture (CLP) models were constructed in wild-type (WT) and pulmonary epithelium-conditional knockout (YAP1f/f) mice to induce ALI, while MLE-12 cells with or without YAP1 overexpression were stimulated by lipopolysaccharide (LPS) in vitro. In vivo modes showed YAP1 knockout aggravated CLP-induced lung injury and also accelerated pulmonary ferroptosis, as presented by down-regulated expression of GPX4, FTH1， and SLC7A11, along with up-regulated expression of SFXN1 and NCOA4. Transcriptome research identified these key genes and ferroptosis pathways involved in sepsis-induced ALI. In vitro modes consistently verified that YAP1 deficiency boosts LPS-driven ferrous iron accumulation and mitochondrial dysfunction in response to LPS. Furthermore, the Co-IP assay revealed that YAP1 overexpression could prevent the degradation of ferritin to an amount of Fe2+ (ferritinophagy) via disrupting NCOA4-FTH1 interaction, which blocked the transport of cytoplasmic Fe2+ into mitochondria via mitochondrial membrane protein (SFXN1), further reduced the generation of mitochondrial ROS. Therefore, these findings revealed that YAP1 could inhibit ferroptosis in a ferritinophagy-mediated manner, thus alleviating sepsis-induced ALI, which may provide a new approach to the therapeutic orientation for sepsis-induced ALI.